A National Library for the 21st century – knowledge and cultural heritage online. Issue 1 (April 2016) - Jøsevold, Roger
Since 2004, the National Library of Norway has worked systematically to develop a digital National Library. The core of this activity has been to digitize the whole collection and to seek ways to disseminate the digital content to the biggest possible audience. Being a true multimedia library, the collection holds published material in a wide spectrum of media: from traditional printed material to radio, TV, audio, film and music. The library also harvests the Norwegian internet domain '.no'. Today the digital library contains 2.8 million digital objects, which adds up to 4000 TB of unique digital content. By use of extended collective licensing everyone with a Norwegian IP address can freely access and read all books published in Norway up to 2001. In addition, through agreements with the major Norwegian newspapers, all Norwegian libraries can offer access to complete digital historical newspaper collections. The most important matter to make this happen has been a strategic partnership and cooperation with rights holders and publishers. This partnership has built trust and confidence and has resulted in a cooperation where knowledge and costs are shared. The National Library of Norway offers digital library services that provide online access to full-text versions of all books published in Norway up until the year 2001, access to digital newspaper collections from the major national and regional newspapers in all libraries in the country, and opportunities for everyone with internet access to search and listen to more than 40, 000 radio programmes recorded between 1933 and the present day. The foundation for this development was laid in 2004 when the National Library adopted a digitization strategy for the creation of a National Library for the 21st century. This was later followed up by the decision in principle in 2006 to digitize the entire collection.